Methodology for Assessing Lung Volumes Based on Recording the Biomechanics of Respiratory Movements - I. I. Revinskaya; P. V. Kamlach (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The method for studying the biomechanics of breathing has been developed to determine the volume of inhaled and exhaled air. The technique is based on recording the movements of the walls of the chest and abdomen of a person during breathing. A video camera was used to record movements of the chest and abdominal walls, with a spirometer used as the reference method for measuring lung volumes. According to the proposed technique, studies were conducted among 63 people (age – 18–26 years, body mass index ranged from 18.1–32.6 kg/m2, height – 160–192 cm). Statistical processing of the results showed a strong relationship between the measured volu mes and the relative deviations of the walls of the human chest and abdomen. The developed technique for studying the biomechanics of breathing can be used for indirect assessment of lung volumes.